Post-Supravaginal Hysterectomy for Bladder Flap Hematoma in P3A0 Preterm Delivery by Cesarean Section due to Fetal Distress - Andi Kurniadi; Rose Dita Dita Prasetyawati; Heti Prasekti (National Cancer Center - Dharmais Cancer Hospital, 2022)
Introduction: Bladder flap hematoma (BFH) is a rare complication of cesarean section (CS). BFH appears between the bladder and the lower uterine segment (LUS) when the visceral peritoneal is closed during traditional CS techniques and decreased uterine contractions. Surgery is the treatment of choice for the management of peritoneal closure in CS and the decrease in uterine contractions that cause BFH.Case Presentation: A 35-year-old G3P2A0 underwent a cesarean delivery due to fetal distress. CS was performed with the visceral peritoneal sutured as in the traditional technique. Six hours after CS, there was an increase in abdominal circumference, muscle defenses, hypotension, tachycardia, anemia, and leukocytosis. She had to undergo repeated laparotomy with acute abdomen after CS and hysterectomy because uterine atony was found.Conclusions: BFH can be caused by peritoneal closure during CS and decreased uterine contractions or uterine atony. Although there is no standard protocol for management, surgical approaches for cases with infection or bleeding and hysterectomy are performed to save the patient’s life from uterine atony.